Heterologous expression, characterization and application of a new β-xylosidase identified in solventogenic Clostridium sp. strain BOH3. (April 2018) - Li, Tinggang; Wu, Yi-Rui; He, Jianzhong
Graphical abstract: Highlights: A thermostable β-xylosidase of GH43 was cloned from Clostridium sp. strain BOH3. The recombinant gene product showed optimal activities at pH 5.0-6.0 and 40 °C. The enzyme had high affinity, enzymatic potency and xylose tolerance. Activity of β-xylosidase could be enhanced (>1.6 folds) by addition of Zn 2+ . The enzyme in combination with xylanase had synergy on xylan degradation. Abstract: A β-xylosidase gene (BxylBOH3 ) was identified in a solventogenic bacterium Clostridium sp. strain BOH3, which is a member of the glycoside hydrolase family 43 (GH43). The recombinant enzyme of BxylBOH3 was expressed in Escherichia coli with a high specific activity of 48.7 U/mg and a low Km value of 2.71 mM at an optimal temperature of 40 °C and pH of 5.0-6.0, indicating its high affinity for the substrate and enzymatic potency. Moreover, activity of β-xylosidase can be enhanced (>1.6 times) by addition of Zn 2+ . The concentration of reducing sugar (including xylose and xylooligosaccharides) with the synergism of xylanase and recombinant β-xylosidase was enhanced up to 129.8% (11.93 g/L) after hydrolysis of 30 g/L of xylan for 24 h when comparing with only xylanase (9.19 g/L). Application of this recombinant β-xylosidase together with xylanase improved xylan hydrolysis efficiency, thus leading to increased biofuels productivity from xylan fermented by Clostridium species.